1976
DOI: 10.1111/j.2044-8295.1976.tb01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Homophones as a Function of Cue Words on the Unattended Channel

Abstract: A prediction based on the model of attention advanced by Dixon (1971) wm tested: namely, that responses to homophones presented to one ear, at supraliminal intensities, would be influenced by subliminal cue words presented to the other ear. Considerable support was found for the hypothesis in terms of response latencies, but not in terms of verbal content. It is suggested that these data make it possible to reconcile apparent discrepancies between the results of other recent studies of dichotic listening. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…For example, Henley (1976) and Eich (1984) demonstrated the influence of concurrent subliminal words in one sensory channel upon interpretations of spoken homophones (the sound HARE/HAIR) in a second, attended channel. Mackay (1973) showed that concurrent, unattended words bias the interpretation of attended polysemous words (e.g., BANK related to river or financial institution).…”
Section: Subliminal Primingmentioning
confidence: 97%
“…For example, Henley (1976) and Eich (1984) demonstrated the influence of concurrent subliminal words in one sensory channel upon interpretations of spoken homophones (the sound HARE/HAIR) in a second, attended channel. Mackay (1973) showed that concurrent, unattended words bias the interpretation of attended polysemous words (e.g., BANK related to river or financial institution).…”
Section: Subliminal Primingmentioning
confidence: 97%
“…My review in the target article was indeed selective 3nd intentionally so -although at the time it was probably nearly exhaustive with respect to the existence of SA/CI within the three lines of investigation under scrutiny. Those who think that the data I have been overlooking (Henley 1976;Henley & Dixon 1974;Mykel & Daves 1979) or just mentioning in passing (Philpott & Wilding 1979;Somekh & Wilding 1973) should have been given more weight may concede that, considering the different requirements that have been discussed in the BBS treatment, these data are at least not fully conclusive. Why not try to replicate these results and to build on them?…”
Section: Commentary)mentioning
confidence: 99%
“…This is especially so with studies that involve auditory presentations. Henley (1976), for example, carried out a study considerably more strong methodologically than many of those cited by Holenderand found that responses to homophones presented to one ear at supraliminal intensities were influenced by subliminal cue words presented to the other ear. This study overcomes the difficulty Holender raises with dichotic studies regarding the levels at which stimuli are presented.…”
Section: Continuing Commentarymentioning
confidence: 99%
“…A partir de replicaciones, o introduciendo ciertas variaciones sobre los experimentos ya mencionados, Henley (1976), Marcel y Patterson (1978), Mykel y Daves (1979), obtuvieron también evidencia a favor de la existencia de análisis semántico inconsciente.…”
Section: Percepción Subliminalunclassified
“…Para Henley (1976), «el tiempo de reacción constituye un indicador más sensiblede los efectos de estímulos subliminales (o no atendidos) que las respuestas verbales» (pág. 566).…”
Section: Discriminación Preatencionalunclassified